Modeling of ribonucleic acid–ligand interactions. (14th September 2015) - Stefaniak, Filip; Chudyk, Ewa I.; Bodkin, Michael; Dawson, Wayne K.; Bujnicki, Janusz M.
Abstract : Computational methods play a pivotal role in the early stages of small molecule drug discovery and are widely applied in virtual screening, structure optimization, and compound activity profiling. Over the past half century in medicinal chemistry, almost all the attention has been directed to protein–ligand binding and computational tools were created with such targets in mind. However, with growing discoveries of functional RNAs and their possible applications, RNA macromolecules have gained considerable attention as possible drug targets. This flow of discovery was followed by adapting existing computational tools for RNA applications as well as active development of new RNA‐tailored methods. However, due to the different nature of RNA, especially its tendency to use morphological plasticity (conformational change in ligand binding) this remains a challenging task. The evolution of 'protein‐based' drug discovery and related computational methods offers some clues on possible future directions and developments in modeling RNA interactions with small molecule ligands. WIREs Comput Mol Sci 2015, 5:425–439. doi: 10.1002/wcms.1226 This article is categorized under: Structure and Mechanism > Computational Biochemistry and Biophysics Computer and Information Science > Chemoinformatics Molecular and Statistical Mechanics > Molecular Interactions Abstract :